Fundamental movement skill and physical fitness measures in children with disabilities - Klavina, Aija; Ostrovska, Karina; Campa, Martins (European Journal of Adapted Physical Activity, 2017)
This study aimed to explore fundamental motor skills and physical fitness outcomes in the group of children with visual, physical and intellectual disabilities. Alongside the average data outcomes, possible gender differences in all measures were also explored. In addition, the association between the level of movement performance and physical fitness variables was investigated. Participants were 82 elementary school age children with mild to moderate disabilities (mean age 9.6 years). To assess fundamental movement skills (FMS), children completed the Test of Gross Motor Development (TGMD) -2. Physical fitness was measured by the four tasks including 30 m run, sit-ups, functional reach test, sit and reach test and handgrip strength. The average TGMD-2 score for the study group in locomotor skills corresponded to 6.3 years of age (39.3 points), while in object control skills it was at 6.6-7.6 years of age (30.9-36.3 points). The average scores in the fitness tests were 30.1 cm in the functional reach test, 17.1 kg in Handgrip test, 14.0 rep in Sit up test and 6.78 sec in 30 m run. There were no significant differences in physical fitness tests results between boys and girls. The linear regression results presented that TGMD-2 skills significantly predicted 30 m run test [F(2; 161) = 8.965, p = .000]. Data analyses according to the level of movement performance and physical fitness showed significant associations between FMS outcomes and 30 m run test (p < .05). The present study extended the small body of research on the fundamental motor skills of children with different functional limitations while having potential to participate in daily physical activities.
Keywords: children; disability; fundamental movement skills; physical fitness